Nurse Practitioner: Is It Time to Have a Role in Saudi Arabia? - Hessa A. Almutairi; Kholoud N. Alharbi; Hana K. Alotheimin; Roaa Gassas; Musaad S. Alghamdi; Ayman A. Alamri; Abdulaziz M. Alsufyani; Adel S. Bashatah (Nursing Reports, 2020)
Low recruitment of Saudi nationals into the nursing profession, coupled with a growing population, has led to a severe nursing shortage in Saudi Arabia, particularly of nurses with advanced qualifications in clinical nursing. While the role of nurse practitioner has been successfully integrated into the healthcare systems of the U.S., Canada, the UK and Australia for decades, the advanced practice registered nurse (APRN), which includes nurse practitioners and clinical nursing specialists, is still not being implemented effectively in Saudi Arabia due to a variety of regulatory, institutional and cultural barriers. The author looks at some of those barriers and offers recommendations of how they might be overcome. Given that in many parts of the world, nurse practitioners are considered an essential component to meeting healthcare demands, the author considers the question of whether APRNs can find a role in Saudi Arabia’s healthcare system.